2020
DOI: 10.1177/2325967120952998
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of the Star Repair for Large and Massive Rotator Cuff Tears: A Modified Triple-Row Technique

Abstract: Background: Large and massive rotator cuff repairs constitute a true challenge for arthroscopic shoulder surgeons. Retear rates as high as 20% have been reported after arthroscopic double-row and suture-bridge techniques used for these tears. Hypothesis: A modified triple-row repair will provide satisfactory clinical results with lower risk for retear. Study Design: Case series; Level of evidence, 4. Methods: Between March 2016 and August 2017, a total of 52 patients with large and massive rotator cuff tears r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…In fact, several triple‐row techniques have been documented to enhance the contact area and pressure within the cuff footprint. This is achieved by incorporating an additional middle‐row anchor to secure the leading edge of the cuff to the bone 34,35,40–43 . In contrast, en masse repair techniques disregard the multilayered structure of the rotator cuff and neglect to restore the native superior capsule and cuff insertion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several triple‐row techniques have been documented to enhance the contact area and pressure within the cuff footprint. This is achieved by incorporating an additional middle‐row anchor to secure the leading edge of the cuff to the bone 34,35,40–43 . In contrast, en masse repair techniques disregard the multilayered structure of the rotator cuff and neglect to restore the native superior capsule and cuff insertion.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by incorporating an additional middle‐row anchor to secure the leading edge of the cuff to the bone. 34 , 35 , 40 , 41 , 42 , 43 In contrast, en masse repair techniques disregard the multilayered structure of the rotator cuff and neglect to restore the native superior capsule and cuff insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis revealed that acromioplasty was more common in patients undergoing arthroscopic surgery, suggesting its wide use in diverse shoulder tear cases [ 14 ]. The adaptability in managing extensive acromioplasty, despite possibly increasing short-term postoperative pain, may lead to better long-term outcomes [ 15 ].…”
Section: Discussionmentioning
confidence: 99%